Perbedaan Frekuensi Serangan Asma pada Pasien Dengan dan Tanpa Lingkungan Perokok Tembakau - Lauranita, Neovita Kriesna (Jurnal Kedokteran Indonesia, 2011)
Background: Asthma can be prevented if its pathogenesis is well understood. Poorly controlled asthmamay cause relapse and poor quality of life. Asthma relapse can be prevented by avoiding triggerfactors, one of which is exposure to tobacco smoke. This study aimed to determine the difference inasthma attack frequency between patients with and without tobacco smoke environment.Methods: This study was analytical observational using cross sectional approach. A sample of 60 asthmaticpatients were selected by purposive sampling from May to June 2011 at the Pulmonary Disease Center,RSUD Dr. Moewardi, Surakarta. The independent variable was tobacco smoking environment. Thedependent variable were frequency of asthma attack by symptoms including wheezing, cough, andtightness. The dependent variables were measured by a questionnaire administered to the patientswith controlled asthma at the moment. Difference in asthma attack frequency was presented in meanand SD. Statistical difference in this frequency was tested by Mann-Whitney on SPSS 16.0 for Windows.Results: On average the patients living in tobacco smoking environment had more asthma attackfrequency per week than those without such an environment, including wheezing (4.70 vs. 3.40; p=0.020), coughing (4.37 vs. 2.90; p= 0.005), andtightness (4.70 vs. 3.40; p=0.020).Conclusions: Patients with tobacco smoke environment have more asthma attacks than those withouttobacco smoke environment.Keywords: asthma attacks frequency, smoking environment